Effective leadership style aand organizational communication toward job satisfaction during merger and acquisition (M & A) stage : a case study - Wong, Peter Tzyy Chuan (2008)
This study was done to determine the effective leadership style and organizational communication towards job satisfaction during merger and acquisition stage at CIMB Berhad. The dependent variable in this study is job satisfaction meanwhile the independent variables are transformational leadership style, charismatic leadership style and top-down communication. Furthermore through regression analysis, charismatic leadership style and top-down communication became the dominant factors in affecting job satisfaction. Hence, the findings of this study can be used as a reference in improving job satisfaction during organization change period.